QUALITY CONTROL OF A MARINE ORIGIN BASED HERBO-MINERAL UNANI FORMULATION (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Kushta Marjan (KM) is one well-known formulation prepared from coral used by Unani physicians for effective treatment of a various ailments. Coral is the calcareous skeleton of the minute marine organism and belongs of phylum coelenterate and is used internally in the form of kushta. It is highly efficacious in Cough, Asthma and Anorexia. Till date no scientific work has been performed to establish quality control of KM. In this study we have enlightened the preparation procedures, structural, functional and physico-chemical properties of KM by analyzing it on classical tests along with modern scientific techniques like FTIR (Fourier-transform infrared spectroscopy), TGA (Thermogravimetric Analysis) and DSC (Differential Scanning Calorimetry) to establish its quality control parameters. FTIR spectra showed peaks attributed to calcium oxide, organic matter and several other substances. Total weight loss during TGA was 30.09% and DSC curve showed peaks at 20°C, 65°C, 183°C and 261°C. Since the study has been first of its kind the results obtained might be taken as standard finger print of kushta marjan and might be helpful for further formulation and standardization of KM in routine analysis.